Wait and consult times for primary healthcare services in central Mozambique: a time-motion study. Issue 1 (1st December 2016) - Wagenaar, Bradley H.; Gimbel, Sarah; Hoek, Roxanne; Pfeiffer, James; Michel, Cathy; Cuembelo, Fatima; Quembo, Titos; Afonso, Pires; Gloyd, Stephen; Lambdin, Barrot H.; Micek, Mark A.; Porthé, Victoria; et al.
Abstract : Background: We describe wait and consult times across public-sector clinics and identify health facility determinants of wait and consult times. Design: We observed 8, 102 patient arrivals and departures from clinical service areas across 12 public-sector clinics in Sofala and Manica Provinces between January and April 2011. Negative binomial generalized estimating equations were used to model associated health facility factors. Results: Mean wait times (in minutes) were: 26.1 for reception; 43.5 for outpatient consults; 58.8 for antenatal visits; 16.2 for well-child visits; 8.0 for pharmacy; and 15.6 for laboratory. Mean consultation times (in minutes) were: 5.3 for outpatient consults; 9.4 for antenatal visits; and 2.3 for well-child visits. Over 70% (884/1, 248) of patients arrived at the clinic to begin queuing for general reception prior to 10:30 am. Facilities with more institutional births had significantly longer wait times for general reception, antenatal visits, and well-child visits. Clinics in rural areas had especially shorter wait times for well-child visits. Outpatient consultations were significantly longer at the smallest health facilities, followed by rural hospitals, tertiary/quaternary facilities, compared with Type 1 rural health centers. Discussion: The average outpatient consult in Central Mozambique lasts 5 min, following over 40 min of waiting, not including time to register at most clinics. Wait times for first antenatal visits are even longer at almost 1 h. Urgent investments in public-sector human resources for health alongside innovative operational research are needed to increase consult times, decrease wait times, and improve health system responsiveness.